Decoding GNAO1 mutations using Caenorhabditis elegans model system: past approaches and future prospectives - Yadav, Shubham; Veliventi, Satya Santoshi; Bhandari, Somya; Gangurde, Sakshi; Naik, Shreeya; Bhagwat, Shraddha N.; Kumar, Santosh (Frontiers in Cellular Neuroscience, 2025)
GNAO1 encephalopathies are a group of neglected genetic disorders primarily occurring due to de novo mutations in the Gαo protein-encoding gene. This gene is reported to be highly conserved among Caenorhabditis elegans (C. elegans) and humans, with a sequence similarity of nearly 80%. The C. elegans model system simplifies studying signaling pathways involved in several neurotransmitters, including GPCR pathways. Therefore, using this model system to delineate downstream effectors and clinical targets to Gαo can be highly advantageous. Mutations that cause GNAO1 encephalopathy can be easily replicated in genetically modified and transgenic C. elegans and validated by rescuing phenotypic defects, primarily locomotion and egg-laying defects in worms. Although there are recent technical advancements in understanding the interacting proteins, there are unclear and uncertain hypotheses that explain the effect of Gαo mutations in humans. In terms of the clinical aspect of this disorder, there are no available approved diagnostic procedures to detect GNAO1 encephalopathy in the early stages of life. The present diagnostic procedures reiterate symptoms and overlap with other neurological symptoms, resulting in neglected data of cases. Therefore, here we provide an overview of past research and a perspective of future work, with the primary objective of focusing on GNAO1 encephalopathy and using the C. elegans model system to study these pathogenic variants.